Guest–matrix interactions affect the solvation of cyclodextrin-based polymeric hydrogels: a UV Raman scattering study. Issue 43 (13th October 2016) - Rossi, B.; Venuti, V.; D'Amico, F.; Gessini, A.; Mele, A.; Punta, C.; Melone, L.; Crupi, V.; Majolino, D.; Masciovecchio, C.
Abstract : The effect of guest–matrix interactions on the solvation of cyclodextrin-based polymeric hydrogels is studied by UV Raman experiments. Abstract : The focus of the present work is to shed light on possible modifications of the molecular properties of polysaccharide hydrogels induced by the establishment of specific non-covalent interactions during the loading of a guest compound inside the gel phase. With this aim, a case study of the encapsulation of caffeine (Caf) inside cyclodextrin-based hydrogels, namely, cyclodextrin nanosponges (NS), is systematically investigated here by using UV Raman scattering experiments. The UV Raman spectra of the hydrogels, analysed as a function of temperature, concentration of the guest molecule loaded in the gel phase and pH, prove particularly informative both on the structural rearrangements of the hydrophobic/hydrophilic groups of the polymeric network and on the breaking/formation of specific guest–matrix interactions. Analysis of the temperature dependence of dynamical parameters, i.e., the dephasing time associated with specific vibrational modes of the polymer backbone, enables the proposal of a molecular picture in which the loading of Caf in NS hydrogels tends to favour access of the water solvent to the more hydrophobic portions of the polymer matrix, which is in turn reflected in a marked increase in the solvation of the whole system. The achievements of this work appear of interest with respect to the design of new possible strategies for controlling the diffusion/release of bioactive molecules inside hydrogel networks, besides corroborating the potential of UV Raman scattering experiments to give new molecular insights into complex phenomena affecting hydrogel phases.